Project-Based Learning dalam Pembelajaran Proyek IoT untuk Meningkatkan Computational Thinking dan Kolaborasi Siswa: Tinjauan Literatur Sistematis - Rosa, Elisa; Nursalman, Muhammad; Rasim, Rasim (JURNAL PETISI (Pendidikan Teknologi Informasi), 2025)
This study is a systematic literature review aimed at examining how the Project-Based Learning (PjBL) approach is applied in Internet of Things (IoT) project-based learning and its impact on the development of students' computational thinking (CT) and collaboration skills. Although few studies explicitly connect these three elements simultaneously, several studies indicate that Arduino-based projects, Scratch, and engineering principles within the PjBL context can support the enhancement of CT and collaboration, especially through interdisciplinary STEM-based approaches. The review findings suggest that IoT project-based learning with a PjBL framework holds strong potential to foster 21st-century skills. However, there remains a gap in developing integrated learning systems that combine PjBL, IoT, CT, and collaboration in a cohesive manner. Therefore, further empirical research is needed to design innovative learning models that are effective within the context of Informatics education in the digital era.